Effects of Yarn Twist Levels on Percentage Reflectance of Cotton Fabrics Woven with Various Constructional Parameters. Issue 1 (January 2015) - Ömeroğlu, Sunay; Akgun, Mine; Becerir, Behcet
Percentage reflectance of plain, twill, and sateen fabrics woven from cotton yarns having various yarn counts and twist levels were presented. Yarn hairiness, fabric thickness, and fabric bulk density that changed with different twist levels were assessed with fabric percentage reflectance. All measured values changed between samples according to yarn twist levels in different ways. Percentage reflectance of fabric samples increased until yarns reached a certain twist level, then decreased with further yarn twist increases. This relationship between fabric percentage reflectance and yarn twist levels was more readily observed in less compact fabrics (fabrics having a low fabric cover factor, low fabric bulk density, and low yarn intersection numbers). Fabric bulk densities and fabric thickness values changed in accordance with yarn twist levels and fabric percentage reflectance.